Work and life animated: A look from the works by David Doutel and Vasco Sá - Veloso, L. (Perspectives of Portuguese animation: David Doutel and Vasco Sá, 2024)
This article presents an analysis of three films by David Doutel and Vasco Sá – Augur (2018), Soot (2014) and The Shoemaker (2011) –, a defying challenge proposed by Pedro Serrazina, since I do not master the language of animated film. This challenge complements another one I embarked on a few years ago, and which took the form of research about the representations of work in Portuguese cinema (Vidal & Veloso, coord., 2016). I will invoke it in this text in the sense of creating cross-readings about artistic creation. I chose to carry out an approach that favours the elements that are common to the three films. This results from a professional practice, which leads me to look at the social regularities, rather than the singularities, but which I believe has the merit of asserting that the singularities are, in turn, social, that is, they allow the understanding of social realities. These films are like this too: singular stories, of unique characters that mirror structural traits of the society3. Their biographies are, thus, socialised biographies. I therefore seek to contribute with a sociological analysis of these three films, hoping to build bridges between scientific work and artistic creation, a belief that has accompanied me for several years in my personal and professional career.